Correlates of post-traumatic stress among victimized women on probation and parole. (March 2022) - Prost, Stephanie Grace; Golder, Seana; Higgins, George E.; Pettus-Davis, Carrie; Renn, Tanya; Edmond, Tonya; Logan, TK
The current study aimed to identify the correlates of post-traumatic stress among a sample of women on probation and parole with a history of victimization. Community-based sampling was used to recruit 406 women on probation and parole in Jefferson County, Kentucky. The post-traumatic stress diagnostic scale was used to measure three indicators of post-traumatic stress: post-traumatic stress disorder diagnosis, symptom severity, and the number of life domains impacted by symptoms. Shaped by the comprehensive health seeking and coping paradigm, logistic and ordinary least squares regression analyses were used to examine the relationships between sociodemographic factors, criminal justice involvement, cumulative victimization, substance use, social support, material loss, homelessness, and post-traumatic stress. Models identifying correlates of post-traumatic stress accounted for between 18.6% and 26% of the variance and point to critical opportunities for intervention surrounding the dynamic factors of recent intimate partner violence and material loss. Targeting these important factors during community supervision is anticipated to decrease post-traumatic stress and increase the likelihood of success under criminal justice system supervision.